so sánh :
b) 5^2000 và 10^1000 c) 2^100; 3^75; 5^50 d) 9^99 và 99^9
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
`x - ( 5/4 - 7/5) = 9/20`
`x- (-3)/20 = 9/20`
`x + 3/20 = 9/30`
`x = 9/30 - 3/20`
`x=6/20`
`x= 3/10`
__________________________
`9-x = 8/7 - (-7/8)`
`9 - x = 8/7 + 7/8`
`9 - x= 113/56`
`x = 9 - 113/56`
`x= 391/56`
= x - ( -3/20) = 9/20
= x= 9/20 + ( -3/20)
= x=3/10
___________________________________
= 9-x=113/56
= x=9- 113/56
= x=391/56
`-1,2+(-0,8)+0,25+5,75-2021`
`=[-1,2+(-0,8)]+(0,25+5,75)-2021`
`=-2+6-2021`
`=4-2021=-2017`
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
`17/11-(6/5-16/11)+26/5`
`=17/11-6/5+16/11+26/5`
`=(17/11+16/11)+(-6/5+26/5)`
`=33/11+20/5`
`=3+4=9`
` -1,2 + (-0,8) + 0,25 + 5,75 - 2021`
` = (-1,2 + (-0,8) )+ (0,25 + 5,75) - 2021`
`= -2 + 6 - 2021`
` = 4 - 2021`
` = -2017`
___________________________________
`17/11 - ( 6/5 - 16/11) + 26/5`
`= 17/11 - 6/5 + 16/11 + 26/5`
` = ( 17/11 + 16/11) + ( -6/5 + 26/5)`
` = 33/11 + 20/5`
`= 3 + 4`
` =7`
a, ( x - \(\dfrac{1}{2}\))0 = 0 ⇔ x - 1/2 = 0 ⇒ x =1/2
b, (x - 2)2 = 1 ⇒ x - 2 = 1 hoặc x -2 = -1
x -2 = 1 ⇒ x = 2 + 1 = 3
x - 2 = -1 ⇒ x = 2 - 1 = 1
vậy x ϵ {1; 3}
c, (2x - 1 )3 = - 8 ⇒ (2x - 1)3 = (-2)3 ⇒ 2x - 1 = -2
⇒ 2x = 1 - 2 = -1⇒ x = -1/2
d, (x + \(\dfrac{1}{2}\))2 = \(\dfrac{1}{16}\) ⇒ ( x+ \(\dfrac{1}{2}\))2 =( \(\dfrac{1}{4}\))2
x + \(\dfrac{1}{2}\) = \(\dfrac{1}{4}\) hoặc x + \(\dfrac{1}{2}\) = - \(\dfrac{1}{4}\)
x + \(\dfrac{1}{2}\) = \(\dfrac{1}{4}\) ⇒ x = \(\dfrac{1}{4}\)- \(\dfrac{1}{2}\)= \(\dfrac{-1}{4}\)
x + \(\dfrac{1}{2}\) = - \(\dfrac{1}{4}\) ⇒ x = -\(\dfrac{1}{2}\) - \(\dfrac{1}{4}\) = \(\dfrac{-3}{4}\)
vậy x ϵ {-\(\dfrac{3}{4}\), - \(\dfrac{1}{4}\)}
a. \(\left(5x-1\right)^6=3^6\\ 5x-1=3\\ 5x=4\\ x=\dfrac{4}{5}\)
b. \(\left(2x+1\right)^3=\left(-0,1\right)^3\\ 2x+1=-0,1\\ 2x=-0,1-1\\ 2x=-1,1\\ x=-0,55\)
(5x-1)6 = 729
(5x-1)6 = 36
5x - 1 = - 3 hoặc 5x - 1 = 3
5x - 1 = -3
x = (-3 + 1) : 5 = -2/5
5x - 1 = 3
5x = 3 + 1
5x = 4
x = 4/5
vậy x ϵ {-2/5; 4/5}
b, (2x + 1)3 = -0,001 = (-0,1)3
2x + 1 = -0,1
2x + 1 = -0,1 - 1 = -1,1
x = -1,1 : 2
x = -0.55
x < \(\dfrac{x+y}{2}\) < y
ta có x + x < x + y < y + y (vì x< y)
⇔2x < x + y < 2y
⇔\(\dfrac{2x}{2}\) < \(\dfrac{x+y}{2}\) < \(\dfrac{2y}{2}\)
⇔ x < \(\dfrac{x+y}{2}\) < y (ddpcm)
so sánh hã bạn?
hello